1996
DOI: 10.1097/00005537-199608000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sinusitis in Cystic Fibrosis

Abstract: It has been pediatric dogma that most children with cystic fibrosis (CF) have pansinusitis and few are symptomatic. To reassess this premise, we compared symptoms, clinical examinations, radiographic and surgical findings, and results of treatment in 19 children with cystic fibrosis who had undergone computed tomography at St. Christopher's Hospital (Philadelphia) from 1991 to 1994. We found two distinct patterns of sinus disease: chronic sinusitis (n = 3) and polyposis (n = 12). Two of the patients with polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
3
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 15 publications
2
91
3
2
Order By: Relevance
“…Secretions in general, and the air-surface liquid in particular, become viscous and stagnant in CF patients, impairing MCC, and contributing to frequent bouts of CRS in the upper airway and bronchopulmonary disease in the lower airway. CF patients have an incidence of RS approaching 100% 1458 and 44% to 58% have NPs. 1459,1460 Medical management in adult and pediatric CF includes nasal saline, INCS, topical antibiotics, dornase alfa, and oral macrolides.…”
Section: Xiic Rs Special Considerations: Cfmentioning
confidence: 99%
“…Secretions in general, and the air-surface liquid in particular, become viscous and stagnant in CF patients, impairing MCC, and contributing to frequent bouts of CRS in the upper airway and bronchopulmonary disease in the lower airway. CF patients have an incidence of RS approaching 100% 1458 and 44% to 58% have NPs. 1459,1460 Medical management in adult and pediatric CF includes nasal saline, INCS, topical antibiotics, dornase alfa, and oral macrolides.…”
Section: Xiic Rs Special Considerations: Cfmentioning
confidence: 99%
“…1 CF patients have a high prevalence (approaching 100%) of severe chronic rhinosinusitis (CRS), which is often associated with nasal polyposis (6-48%). [2][3][4][5] The pathophysiology of CRS in CF patients is because of, in large part, impaired mucociliary clearance (MCC)-a critical host defense mechanism for maintaining healthy sinuses in normal individuals. 6 Although pulmonary failure leads to the ultimate demise of most CF patients, CRS has a significant impact on their overall quality of life and may contribute to lung disease pathogenesis.…”
mentioning
confidence: 99%
“…3 Theoretic explanations for patients with CF underreporting their sinus symptoms include the early onset of CRS in childhood, causing a lack of awareness of a symptom-free state; or masking of their sinus symptoms by the severity of their other medical issues. 3,4 Despite limited subjective reporting of clinical symptoms, some studies [5][6][7][8] have demonstrated relationships between clinical indicators and the severity of sinus disease in these children. There has historically been limited interdisciplinary coordination between physicians who primarily treat patients with CF and otolaryngologists at our institution, owing to the relative underreporting of symptoms.…”
mentioning
confidence: 99%